Distance dilution of antibiotic resistance genes of sediments in an estuary system in relation to coastal cities. (15th July 2021) - Lu, Xiao-Ming; Peng, Xin; Xue, Feng; Qin, Song; Ye, Shen; Dai, Li-Bo
Abstract: Coastal tourist and industrial cities are most likely to have differential effects on the distance dilution of antibiotic resistance genes (ARGs) in an estuary system. This study used high-throughput fluorescence quantitative polymerase chain reaction to identify sediment ARGs in two typical estuaries of coastal tourist and industrial cities (Xiamen and Taizhou) in China. The distance dilution of ARGs and its relationship with key environmental factors were analysed. The results indicated that along the river inlet towards the sea, the distance dilution effect on ARG abundance in estuary sediments of Taizhou was approximately double that in Xiamen, and the macrolide, lincosamide, and streptogramin B (MLSB) and vancomycin genes were replaced by the fluoroquinolone, quinolone, florfenicol, chloramphenicol, and amphenicol (FCA) and β-lactam genes in Taizhou, whereas β-lactam genes succeeded the MLSB and sul genes in Xiamen. The abundance and number of ARGs and mobile genetic elements (MGEs) were positively correlated with the particle size and total organic carbon (TOC) contents of sediments, whereas they were negatively associated with the oxidation and reduction potential ( E h ) and pH of sediments, as well as the seawater salinity. The sediment particle size (SPZ) was the dominant physicochemical factor affecting the abundance of ARGs ( r  = 0.826, p  < 0.05) and MGEs ( r  = 0.850, p  < 0.01). These findings suggest that although the distance dilution effect on the ARG abundance of estuary sediments of the industrial city is greater than that of the tourist city, the larger SPZ, higher TOC content, and lower salinity, pH, and E h in estuary regions adjacent to the industrial city can more significantly facilitate the proliferation and propagation of ARGs in the sediments. Graphical abstract: Image 1 Highlights: Distance dilution of estuarine ARGs in industrial city exceeded that of tourist city. From river inlet to the sea, β-lactam ARGs replaced MLSB ARGs in estuary sediments. Sediment particle size was the dominant physicochemical factor for the ARG abundance. Salinity, oxidation and reduction potential, and pH were negatively related to ARGs.